HUBUNGAN KEPUASAN PELAYANAN MAKANAN DAN SISA MAKANAN DENGAN KECUKUPAN GIZI PADA PASIEN KELAS III DI RUMAH SAKIT - Ima Mega Puspa; Dyah Nur Subandriani; J. Supadi (Poltekkes Kemenkes Semarang, 2019)
Background : Satisfaction of patients is one of success indicator of hospital food management that influence the nutritional adequacy of patients. The satisfaction of patients can be seen from the taste, punctuality of distribution, waiter hospitality and the cleanliness of tools. The other quality indicators of nutrition services is leftovers.Objectives : Reviewing the relationship of the satisfaction of food and rest service satisfaction with nutritional success in class III patients in the Roemani Hospital of Muhammadiyah Semarang.Method : This study is descriptive analytic study by using cross sectional design. The taking of sample was done by concecutive sampling and it was gotten with 30 samples. The data collection was done by interview used the questionnaire guide of the satisfaction of hospital food, recall 24 hours to know the outside intake of hospital, weighing and observation of leftovers, also counting the nutritional adequacy by comparing nutritional intake from food and nutrinionl adequacy. The data was prosseced by chi square test.Results : The subject have good perception to the food service of hospital as much as 63,3%, leftovers beetween 56,7%, and nutritional adequacy as much as 96,7%. Conclusion : There is no urgent relation beetween satisfaction based on food service and leftovers to nutritional adequacy level.